Phase II Trial of Gefitinib 250 mg Daily in Patients with Recurrent and/or Metastatic Squamous Cell Carcinoma of the Head and Neck - Cohen, Ezra E.W.; Kane, Madeleine A.; List, Marcy A.; Brockstein, Bruce E.; Mehrotra, Bhoomi; Huo, Dezheng; Mauer, Ann M.; Pierce, Carolyn; Dekker, Allison; Vokes, Everett E. (Clinical cancer research, 2005)
Purpose: An objective response rate of 11% was reported in patients with recurrent and/or metastatic squamous cell carcinoma of the head and neck (SCCHN) treated with 500 mg daily gefitinib although the recommended dose in lung cancer is 250 mg. This study evaluated the efficacy and toxicity of 250 mg daily gefitinib in patients with recurrent and/or metastatic SCCHN. Experimental Design: Phase II trial with objective response rate as the primary end point. Measurements of quality of life and levels of serum vascular endothelial growth factor and transforming growth factor-α were assessed before and during therapy. Results: In 70 patients, 1 (1.4%) partial response was observed. Median progression-free survival and overall survival were 1.8 and 5.5 months, respectively. Quality of life scores improved transiently during the first weeks of therapy before returning to baseline. Median vascular endothelial growth factor and transforming growth factor-α levels were above the normal range but were not predictive of outcome. Four patients experienced grade 3 drug-related adverse events. Rash of any grade was observed in 64% of subjects. Correlation between disease control (partial response + stable disease), progression-free survival, and overall survival and grade of cutaneous toxicity was observed ( P = 0.001, 0.001, and 0.008 respectively). Conclusions: Gefitinib monotherapy at 250 mg in recurrent and/or metastatic SCCHN seems to have less activity than was previously observed for 500 mg daily. A dose-response relationship may exist for this agent in SCCHN and grade of cutaneous toxicity attributable to gefitinib is a clinical predictor of better outcome.